Interventions for Addressing Anemia Among Children and Adolescents: An Overview of Systematic Reviews - Mithra, Prasanna; Khatib, Mahalaqua Nazli; Sinha, Anju Pradhan; Kumar, Nithin; Holla, Ramesh; Unnikrishnan, Bhaskaran; Vijayamma, Ratheebhai; Nair, N. Sreekumaran; Gaidhane, Abhay; Quazi Zahiruddin, Syed (Frontiers in Pediatrics, 2021)
Context: Anemia is a public health problem. Anaemic states can lead to impairments associated with growth, cognitive and motor development. Objective: To collate evidence on interventions for addressing childhood and adolescent anaemia. Methods: In this overview of systematic reviews, we included Cochrane as well as non-Cochrane systematic reviews (SRs) irrespective of language and publication status. Two sets of review authors independently screened articles for eligibility and extracted data from relevant SRs. We presented data in tabular format and summarized results based on outcome reported age of participants and type of interventions. We also adopted a ‘measurement for change’ approach to assessing the utility of measurement for change of interventions in childhood and adolescent anaemia. Results: Our search yielded 2601 records of which 31 SRs were found eligible for inclusion. Results were favourable for fortification and supplementation, with a clear reduction in the risk of anaemia and an increase in haemoglobin levels across all age groups. Other interventions reported by the SRs were inconclusive and suggests further research. Conclusions: Current evidence suggests that fortification or supplementation with iron and micronutrients leads to better reduction in the risk of anaemia and improvements in hemoglobin levels among children and adolescents. Results of this overview can help decision makers for informing selection of interventions to address childhood and adolescent anaemia.